Products of normal locally supersoluble subgroups - Reyes, Allan S. (Animo Repository, 2015)
Classes of groups are not necessarily closed under forming products. That is, if a group G that is the product of H and K, where H and K are normal locally supersoluble subgroups of G, then G need not be locally supersoluble. This paper determines sufficient conditions for H so that G would be locally supersoluble and further identifies classes of groups that satisfy these conditions: periodic locally soluble CC-groups that are PST-groups, radical hyperfinite AP-groups, and periodic radical PT-group satisfying min-p for all primes p.